2-amino-5-chloropyrimidin-1-ium hydrogen maleate - Fun, Hoong-Kun. (2013)
In the title salt, C4H5ClN3+·C4H3O4-, the 2-amino-5-chloropyrimidinium cation is protonated at one of its pyrimidine N atoms. In the roughly planar (r.m.s. deviation = 0.026 Å) hydrogen malate anion, an intramolecular O-HO hydrogen bond generates an S(7) ring. In the crystal, the protonated N atom and the 2-amino group of the cation are hydrogen bonded to the carboxylate O atoms of the anion via a pair of N-HO hydrogen bonds, forming an R22(8) ring motif. The ion pairs are connected via further N-HO hydrogen bonds and a short C-HO interaction, forming layers lying parallel to the bc plane.